Do lixo ao luxo: sistema de transporte para materiais de desenho de baixo custo para discentes do curso de Design - Gomes, Jordana Santiago (Brasil, 2025)
This Final Graduation Project presents the development of a transportation system for drawing materials, named "Moochila." The project addresses three main issues: the environmental impacts of improper disposal of solid waste, the economic inequality that hinders access to specialized products, and the need for greater practicality in urban mobility for design students. The main objective was to develop an eco-efficient, functional, and low-cost transportation system using long-life packaging as the primary raw material. The methodology followed the steps proposed by Bruno Munari, complemented by contributions from other authors, such as Baxter and Kano, encompassing analysis of similar products, questionnaires, and studies on the properties of carton packaging to support the development of the final product. The project achieved its objectives by transforming waste into functional and sustainable products, promoting the circular economy, and meeting the practical, emotional, and cultural needs of its target audience.